Підхід до стратегічного управління персоналом підприємства - Щербань, О. Д.; Shcherban, O. D. (Херсонський державний аграрно-економічний університет, 2025)
У сучасних умовах стрімких змін зовнішнього середовища стратегічне управління пер- соналом стає ключовим для адаптації та конкурентоспроможності підприємств. Акцент зміщується на нематеріальні активи, особливо інтелектуальний та соціальний капітал, но- сіями яких є персонал. Стратегічне управління персоналом – це довгостроковий підхід, інте- грований із загальною стратегією розвитку компанії, враховує вплив зовнішніх/внутрішніх факторів та ринку праці. Він вимагає якісних змін у кадровій роботі: стратегічне плануван- ня, організація та контроль персоналу замінюють традиційні методи. Основними завдан- нями є формування та розвиток людського потенціалу, маркетинг талантів, вдосконалення відбору, оцінки, навчання, трудових відносин та інформаційного забезпечення. Стратегічне управління персоналом спрямоване на узгодження цілей компанії з можливостями та інтер- есами співробітників, підвищення їх мотивації, розкриття творчого потенціалу та забез- печення конкурентних переваг через ефективне використання людських ресурсів.

In today's volatile business landscape, characterized by technological disruption, globalization, and shifting socio-economic paradigms, the imperative for organizations to adopt Strategic Human Resource Management (SHRM) has become undeniable. SHRM transcends mere personnel administration, positioning human capital as the central driver of sustainable adaptation and competitive advantage. Modern enterprises must fundamentally reorient their focus from compliancecentric management of tangible assets towards the proactive cultivation and optimization of intangible assets—specifically, the intellectual capital (knowledge, skills, creativity) and social capital (networks, relationships, collaboration) inherent in their workforce. SHRM is defined by its intrinsic long-term perspective, its deep integration with the overarching organizational strategy and objectives, and its dynamic responsiveness to multifaceted external factors (economic shifts, technological advancements, regulatory changes, competitive pressures) and internal dynamics (organizational culture, structure, leadership) alongside evolving labor market trends. This strategic shift necessitates profound qualitative transformations across all HR functions. Traditional reactive personnel management is supplanted by a proactive, holistic approach encompassing strategic workforce planning, organizing structures and roles aligned with future needs, and controlling performance through a strategic lens. Core dimensions of SHRM include the systematic development and maximization of human potential, sophisticated talent marketing strategies (encompassing granular labour market analysis, employer branding, and predictive recruitment systems), comprehensive overhaul of selection methodologies and assessment tools to identify strategic talent, redesign of training and development programs for future capability building, fostering constructive labour relations and engagement, and elevating HR information systems to a truly strategic decision-support level capable of predictive analytics.
Approach to strategic human resource management of the enterprise
Keywords: стратегія; управління персоналом підприємства; цілі; шляхи реалізації; етапи; ефективність управлінської діяльності; strategy; enterprise human resource management; objectives; implementation pathways; stages; management effectiveness